2019
DOI: 10.15537/smj.2019.5.24096
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seasonal changes in temperature and humidity on incidence of necrotizing soft tissue infections in Halifax, Canada, 2001-2015

Abstract: Objectives: To explore weather seasonal variation in Necrotizing soft tissue infections (NSTI) in Halifax, Nova Scotia, Canada could be attributed to changes in environmental factors of temperature and humidity specifically. Methods: A retrospective chart review of NSTIs between 2001 and 2015. Regional temperature and humidity data were obtained from the Environment Canada Agency, Halifax, Canada. Chi-square was used for categorical variables and continuous data was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Streptococci and anaerobes are more often involved where temperatures rise. 16 As in our study, a male predominance was found in many cosmopolitan studies. The exception seems to be sub-Saharan Africa where the sex ratio is reversed with a female predominance.…”
Section: Discussionsupporting
confidence: 77%
“…Streptococci and anaerobes are more often involved where temperatures rise. 16 As in our study, a male predominance was found in many cosmopolitan studies. The exception seems to be sub-Saharan Africa where the sex ratio is reversed with a female predominance.…”
Section: Discussionsupporting
confidence: 77%
“…This correlation between NSTIs and warmer climates is well described in the literature [9]. Furthermore, there exists a pattern of seasonal variations within individual countries, with more infections occurring during the summer compared to colder seasons [10].…”
Section: Incidence and Epidemiologymentioning
confidence: 56%